Wayang dalam Tari Sunda Gaya Priangan - Rusliana, Iyus (PANGGUNG, 2016)
ABSTRACTÃÂ This paper is a study on the potential ÃÂ of puppet (wayang) ÃÂ in the scope of Sundanese ÃÂ culture of ÃÂ Priangan subculture, ÃÂ especially ÃÂ dance. ÃÂ Formerly ÃÂ the term ÃÂ of wayang ÃÂ means ÃÂ to call dolls made of wood which ÃÂ are ÃÂ played ÃÂ by a puppeteer (dalang) ÃÂ in a performance ÃÂ of puppetry ÃÂ art or to tell ÃÂ the story ÃÂ of its performance, ÃÂ andÃÂ  it is also directly ÃÂ to call the art of WayangÃÂ  ÃÂ Golek puppetry. Later, the potential ÃÂ of wayang affects strongly ÃÂ to the various ÃÂ aspects of life which are related ÃÂ to belief and art, including ÃÂ to Sundanese ÃÂ dance of Priangan style. Since ÃÂ wayang con- sists of religious sense which is implied in the story, thus wayang in Sundanese ÃÂ dance of Priangan style is not ÃÂ separated from the mission ÃÂ or moralÃÂ  value to the guidance ÃÂ of life. The emerge of Wayang Wong Priangan ÃÂ revealed as a dance drama with dialogue carrying ÃÂ the story of wayang in complete or partly, ÃÂ and there are always, ÃÂ conflicts ÃÂ between the evil wayang ÃÂ characters ÃÂ and the ones who extinguish ÃÂ the evils.ÃÂ Keywords: Priangan subculture, Wayang Dance, Priangan styleÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Tulisan ini merupakan kajian terhadap potensi wayang dalam lingkup budaya Sunda subkultur Priangan, khususnya seni tari. Awalnya kata wayang diartikan untuk menyebut boneka dari kayu yang dimainkan dalang dalam pertunjukan seni pedalangan atau untuk menunjukkan ceritanya dalam pertunjukan seni padalangan, dan juga bisa secara langsung untuk menyebut seni padalangan Wayang Golek. Selanjutnya potensi wayang ini berpengaruh kuat ke dalam beberapa aspek kehidupan yang berbau kepercayaan dan juga kesenian, termasuk ke tari Sunda gaya Priangan. Karena wayang mengandung makna religius yang tersirat dalam isi ceritanya, maka wayang dalam tari Sunda gaya Priangan tidaklah lepas dari misi atau pesan moral ke arah tuntunan hidup. Lahirnya Wayang Wong Priangan, terungkap sebagai bentuk dramatari berdialog dengan membawakan cerita wayang secara utuh atau sebagian, dan senantiasa adanya pertentangan antara tokoh wayang yang jahat dengan yang menumpas kejahatan.ÃÂ Kata kunci: subkultur Priangan, Tari Wayang, gaya Priangan